Protein-protein interactions between A. aegypti midgut and dengue virus 2: two-hybrid screens using the midgut cDNA library - Tham, Hong-Wai; Balasubramaniam, Vinod R. M. T.; Chew, Miaw-Fang; Ahmad, Hamdan; Hassan, Sharifah Syed (The Journal of Infection in Developing Countries, 2015)
Introduction: Dengue virus (DENV) is principally transmitted by the Aedes aegypti mosquito. To date, mosquito population control remains the key strategy for reducing the continuing spread of DENV. The focus on the development of new vector control strategies through an understanding of the mosquito-virus relationship is essential, especially targeting the midgut, which is the first mosquito organ exposed to DENV infection. Methodology: A cDNA library derived from female adult A. aegypti mosquito midgut cells was established using the switching mechanism at the 5’ end of the RNA transcript (SMART), in combination with a highly potent recombination machinery of Saccharomyces cerevisiae. Gal4-based yeast two-hybrid (Y2H) assays were performed against DENV-2 proteins (E, prM, M, and NS1). Mammalian two-hybrid (M2H) and double immunofluorescence assays (IFA) were conducted to validate the authenticity of the three selected interactions. Results: The cDNA library was of good quality based on its transformation efficiency, cell density, titer, and the percentage of insert size. A total of 36 midgut proteins interacting with DENV-2 proteins were identified, some involved in nucleic acid transcription, oxidoreductase activity, peptidase activity, and ion binding. Positive outcomes were obtained from the three selected interactions validated using M2H and double IFA assays. Conclusions: The identified proteins have different biological activities that may aid in the virus replication pathway. Therefore, the midgut cDNA library is a valuable tool for identifying DENV-2 interacting proteins. The positive outcomes of the three selected proteins validated supported the quality of the cDNA library and the robustness of the Y2H mechanisms.